Knowledge of Parents with Children with Special Needs about Covid-19 in Children - Wahyu Ersila; Lia Dwi Prafitri; Nuniek Nizmah Fajriyah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
In Indonesia, the increasingly rapid spread of the Covid-19 virus has an impact on many areas of life, from the economy to society, culture and education. Children with disabilities are at greater risk of contracting Covid-19 health-related challenges and inability to understand and follow definite measures for infection control. So that people's knowledge is needed. It is very important to explain methods that can help prevent COVID 19 in children. Parents are role models and advocates for their children's health. Therefore, it is very important to know the knowledge of parents about COVID 19 including clinical signs, modes of transmission, and ways of prevention. The purpose of this study was to determine parental knowledge about Covid 19 in children at the Wiradesa State Special School, Pekalongan Regency. The research method uses a descriptive type with a cross sectional approach, the number of samples is 48 simple random sampling technique. The research instrument used a questionnaire. The analysis used is univariate. The results of the study obtained that most of the parents' knowledge was in the sufficient category, 48%. So that through the results of this study, it can be considered to increase parental knowledge through health education about Covid 19 for parents with children with special needs.